SIFAT-SIFAT TEKNIS CAMPURAN LASTON YANG MENGANDUNG BIOASPAL UNTUK KATEGORI LALU LINTAS BERAT DENGAN PENGUJIAN MARSHALL IMMERSION - , HALIMATU SADIAH, Ir. Heru Budi Utomo, MT. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Asphalt is processed waste oil used for highway pavement. In general, the existing asphalt pavement in the field is produced by PT. Pertamina from the rest of refined petroleum. The cost of production of petroleum asphalt tend to be expensive to make an excuse to produce bitumen from other raw materials cheaper. Raw materials, from oil palm shell liquid smoke called bio asphalt. The initial process of making bio-asphalt is preceded by pyrolysis process in advance to get the tar and oil palm shell liquid smoke. After the results obtained from the pyrolysis process, is the process of distillation to vaporize liquid smoke residue and precipitate who called bio asphalt. Bio asphalt that have been obtained will then be a matter for mixing asphalt with notes pertamina not reduce the quality of the asphalt Pertamina. Mixing bio bitumen asphalt against Pertamina is 1 % - 10 % of the weight of asphalt pertamia that will be tested. Tests performed include penetration testing asphalt, asphalt density testing, testing softening point, and ductility testing to determine the engineering properties of mixing between Pertamina and bio bitumen asphalt in order to obtain the maximum level of the asphalt mixing. Distilled asphalt tend not to harden, then combined with the asphalt pavement from Pertamina to do some testing first. After doing some testing at the end of bio Obtain maximum mixing asphalt with asphalt pertamina appropriate quality requirements by mixing asphalt is asphalt Pertamina 99% and 1% bio asphalt. The percentage of eligible asphalt is then further testing using testing aggregate LASTON ie marshall and marshall immersion testing to determine the engineering properties of mixtures containing LASTON bioaspal for heavy traffic category.